GEOMETRY MODEL HYDRAULIC FRACTURING STIMULATION OF SHALE GAS RESERVOIR - ZAKIY YUSRIZAL (NIM: 22215032), MUHAMMAD
Natural gas production from shale rock formations that rich in hydrocarbon, known as “shale gas”, is one of the fastest growing trends in onshore oil and gas exploration in US nowadays. Exploration, drilling and production of shale gas at Barnett, Fayetteville and Haynesville Shale have transformed the nonconventional gas industry and are crucial in shale gas development in other parts of the US. Technologies that help further shale gas development are horizontal drilling and hydraulic fracturing. In this research, conducted with the help of software to get the fracture geometry model and proppant distribution and other software for experimental method that is grouping the output data of the hydraulic fracturing software to facilitate identify the result of geometry fracture output and proppant distribution as well. From the combination of the software, the longest fracture length is obtained by the combination of 2% KCl fracture fluid with a Black Plus 20/40 proppant with a length of 154.10 ft, the highest total fracture height generated by the DF20020G2K fracture fluid as well as the combination of proppant Black Plus 20/40 with 334.30 ft height created from depth of 7618 ft to 7952.3 ft, the widest average width fracture of 3.35 in (0.28 ft) with SPEC_4000_1 fracture fluid and also with the same proppant combination that is Black Plus 20/40. For the length of the deepest proppant entering into the fracture, there are 3 proppants with the same value that is Atlas PRC 20/40, Black Plus 20/40, and Precured 20/40 which all are achieved with the same fracture fluid that is 10.00 PPG (21.5%) C with a length of 27.9 ft, the total proppant height that fills the fracture is a proppant Black Plus 20/40 with a combination of DF20020G2K fracture fluid as high as 57.9 ft, highest average proppant concentration is Accupack 20/40 and Brady 20/40 of 1.93 with combination 10.00 PPG (21.5%) C fractional fluid and the largest dimensionless conductivity produced by the Accupack 20/40 proppant with a value of 232.62 from the combination of the SPEC_4000_1 fracture fluid.